CXCL13 as biomarker for histological involvement in Sjögren's syndrome. (4th July 2019) - Colafrancesco, Serena; Priori, Roberta; Smith, Charlotte G; Minniti, Antonina; Iannizzotto, Valentina; Pipi, Elena; Lucchesi, Davide; Pontarini, Elena; Nayar, Saba; Campos, Joana; Arienzo, Francesca; Fusconi, Massimo; et al.
Abstract: Objectives: SS is an autoimmune condition characterized by systemic B-cell activation, autoantibody production and ectopic germinal centres' formation within the salivary gland (SG). The extent of SG infiltrate has been proposed as a biomarker of disease severity. Plasma levels of CXCL13 correlate with germinal centres' activity in animal models and disease severity in SS, suggesting its potential use as a surrogate serum marker to monitor local B-cell activation. The aim of this study was to evaluate the potential role of CXCL13 as a biomarker of SG pathology in two independent SS cohorts. Methods: 109 patients with SS were recruited at Sapienza University of Rome (Italy) ( n = 60), or at Queen Elizabeth Hospital in Birmingham and Barts Health NHS Trust in London ( n = 49). Both sera and matched minor SG biopsy were available. Sicca ( n = 57) and healthy subjects' ( n = 19) sera were used as control. Results: CXCL13 serum level was higher in SS patients compared with controls. Correlations between its serum levels and a series of histomorphological parameters, including size of the aggregates and the presence germinal centres', were observed. Conclusion: Our data foster the use of CXCL13 to monitor the extent of local pathology in SS and its validation in longitudinal clinical studies.